Students’ Critical Thinking Skills Improvement through Community of Lecturer, Teacher, and Colleger (CLTC) - I Nyoman Try Upayogi; H. Riandi; Sumar Hendayana; Ida Kaniawati (PAEDAGOGIA, 2024)
The student's critical thinking skills in Ngada Regency are still relatively low, with an average test score of 44,9. Critical thinking is a fundamental skill that students must possess to face future challenges in the era of global competition. Initial classroom observations indicate that teachers need more facilitation in developing students' critical thinking. Several issues identified include: (a) the provision of information sources is still limited to textbooks, (b) teachers have not facilitated students in asking critical questions (teachers ask more questions, and students answer), (c) teachers lack in providing opportunities for students to conclude in Worksheets or summarize learning outcomes, and (d) student Worksheets mainly involve filling in or explaining terms, lacking opportunities for students to strategize problem-solving. These issues can be addressed through focused and continuous mentoring, necessitating a school learning community. This study investigates the influence of the Community of Lecturers, Teachers, and Colleger (CLTC) on teachers' professional development in enhancing students' critical thinking skills. The study employs a mixed methods case study (MMCS) design to investigate the influence of CLTC on teachers' professional development in improving the critical thinking skills of 8th-grade students in science subjects. Data were collected through interviews, observations, and critical thinking skills tests. Qualitative data were analyzed using a thematic analysis approach, while quantitative data were analyzed using paired t-tests. The results showed increased teachers' professionalism in enhancing students' critical thinking skills during CLTC activities. Statistical tests also showed significant differences in students' critical thinking skills before and after teachers participated in CLTC, with a Sig. (2-tailed) value of 0,015. Classroom observations and sharing during learning evaluations were the most effective activities based on qualitative findings. These findings have implications for universities and schools to create mutually beneficial partnerships to enhance teachers' professionalism and students' experience. The practical implications of this research include recommending that teachers conduct peer teaching observations and sharing sessions within schools routinely. Colleger must also be involved in the learning community at school early in order to form professional teacher candidates earlier